Association of optimal blood pressure with mortality in patients taking antihypertensive medications. Issue 11 (20th September 2020) - Yun, Dong‐Ho; Lee, Hye‐Sun; Choi, Won‐Jun; Chang, Hyuk‐Jae; Son, Da‐Hye; Lee, Ji‐Won
Abstract: We investigated the relationship between blood pressure (BP) and mortality in patients taking antihypertensive medications in the Korean using data from the 2007‐2015 Korean National Health and Nutrition Examination Surveys. A total of 6601 patients aged 30‐74 years were included. Systolic BP (SBP) and diastolic BP (DBP) were both divided into four groups as follows: SBP < 120, 120 ≤ SBP ≤ 129 130 ≤ SBP ≤ 139, and SBP ≥ 140; DBP < 70, 70 ≤ DBP ≤ 79, 80 ≤ DBP ≤ 89, and DBP ≥ 90. The survival rates and hazard ratios were evaluated using Kaplan‐Meier curves and multivariable Cox regression analyses. To evaluate the predictability of all‐cause mortality according to SBP and/or DBP, we calculated Harrell's concordance‐index. The lowest DBP group had a high risk of mortality regardless of the SBP status. The group with DBP < 70 mm Hg and SBP ≥ 140 mm Hg showed the highest mortality. The discriminatory ability calculated using Harrell's C‐indexes was greater for the combination of SBP and DBP compared to DBP or SBP alone. These results suggest that it is more effective to simultaneously evaluate the effect of SBP and DBP to predict mortality; clinicians should manage DBP < 70 mm Hg when treating hypertensive patients.